Cultural Diversity: Exploring Eco-Cultural Memories in Hilary Tham’s Tin Mines and Concubines (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Motivated by the theme of cultural diversity in Hilary Tham’s Tin Mines and Concubines (2005), a Malaysian fiction that depicts various family stories of multiethnic Malaysians in the 1960s, this article examines the ways in which the author draws on her cultural memories of Malaysian society through the lens of ecocriticism. While cultural memories convey the memories embedded in physical monuments, eco-cultural memories signify memories implanted in ecological substances. Eco-cultural memories entwine both natural and cultural aspects and are essential to the subject of ecocriticism, which emphasises human-non-human links. The research sheds light on Malaysia’s varied cultures by examining cultural memories incorporating animal, plant and culinary aspects. Tham’s perceptions of cultural variety vary according to ethnic origins, cultural upbringing, belief systems, social classes, cultural practices and experiences. In general, examining Tham’s eco-cultural recollections about bodily functions, weddings, superstitions, cultural alienation and social class reveals how the organic relationship between the animal, food and plant components fosters intercultural consciousness and interracial mutual understanding and misunderstanding in Malaysian society.